Cardiovascular outcomes with GLP-1 receptor agonists vs. SGLT-2 inhibitors in patients with type 2 diabetes. Issue 6 (2nd July 2021) - Nørgaard, Caroline H; Starkopf, Liis; Gerds, Thomas A; Vestergaard, Peter; Bonde, Anders N; Fosbøl, Emil; Køber, Lars; Wong, Nathan D; Torp-Pedersen, Christian; Lee, Christina J-Y
Abstract: Aims: We examined cardiovascular outcomes associated with initiation of glucagon-like peptide-1 receptor agonist (GLP-1RA) vs. sodium–glucose co-transporter-2 inhibitor (SGLT-2i) treatment in a real-world setting among patients with type 2 diabetes. Methods and results: This Danish nationwide registry-based cohort study included patients with type 2 diabetes with a first-ever prescription of either GLP-1RA or SGLT-2i from 2013 through 2015 with follow-up until end of 2018. All analyses were standardized with respect to age, sex, diabetes duration, comorbidity, and comedication. The main outcome was a composite of cardiovascular death, myocardial infarction, and stroke. Furthermore, the components of the composite outcome and hospitalization for heart failure were evaluated. Standardized average 3-year risks of outcomes and differences thereof were estimated using doubly robust estimation combining cause-specific Cox regression with propensity score regression. We identified 8913 new users of GLP-1RA and 5275 new users of SGLT-2i. The standardized 3-year risk associated with initiating GLP-1RA and SGLT-2i, respectively, was as follows: composite cardiovascular outcome, 5.6% [95% confidence interval (CI): 5.2–6.1] vs. 5.6% (95% CI: 4.8–6.3); cardiovascular mortality, 1.6% (95% CI: 1.3–1.9) vs. 1.5% (95% CI: 1.1–1.8); hospitalization for heart failure, 1.7% (95% CI: 1.5–2.0) vs. 1.8% (95% CI: 1.2–2.5); myocardial infarction, 2.1% (95% CI: 1.8–2.4) vs. 2.1% (95% CI: 1.5–2.6); and stroke, 2.5% (95% CI: 2.2–2.9) vs. 2.6% (95% CI: 2.2–3.1). Conclusion: In this nationwide study of patients with type 2 diabetes, initiating GLP-1RA vs. SGLT-2i was not found to be associated with significant differences in cardiovascular risk.